The Role of Mdivi-1 in Reducing Mitochondrial Fission via the NF-kappaB/JNK/SIRT3 Signaling Pathway in Acute Kidney Injury - Gou, X.-Y; Li, Y; Fan, X.-P (Physiological research, 2025)
To explore the effects and underlying mechanisms of Mdivi-1 on three common clinical models of acute kidney injury (AKI). Three common AKI cell models were constructed, classified into the control group (human renal tubular epithelial cells [HK-2] cells), the Iohexol group (HK-2 cells treated with Iohexol), the Genta group (HK-2 cells treated with Gentamicin), and the Cis group (HK-2 cells treated with Cisplatin). To explore the optimal protective concentration of Mdivi-1 for each AKI cell model, the experimental design consisted of the following seven groups: the control group (HK-2 cells cultured in medium), three injury groups (HK-2 cells subjected to Iohexol, Gentamicin, or Cisplatin), and the corresponding protection groups (with a certain concentration of Mdivi-1 added to each injury group). Cellular survival and apoptosis, reactive oxygen species (ROS) levels, and the expression of recombinant Sirtuin 3 (SIRT3) in each group were measured. Mitochondrial fission and fusion dynamics in cells were observed under an electron microscope. To explore relevant pathways, the changes in relevant pathway proteins were analyzed through Western blotting. The half maximal inhibitory concentration (IC50) values were 150.06 mgI/ml at 6 h in the Iohexol group, 37.88 mg/ml at 24 h in the Gentamicin group, and 13.48 microM at 24 h in the Cisplatin group. Compared with the control group, the three injury groups showed increased cell apoptosis rates and higher expressions of apoptotic proteins in HK-2 cells, with an accompanying decrease in cell migration. After the addition of corresponding concentrations of Mdivi-1, the optimal concentrations were 3 μM in the Iohexo-3 group, 1 microM in the Genta-1 group, and 5 μM in the Cis-5 group, HK-2 cells showed the highest survival rate, reduced apoptosis, decreased mitochondrial ROS and SIRT3 expression, and reduced mitochondrial fission and autophagy when compared with each injury group. Further verification with Western blot analysis after the addition of Mdivi-1 revealed a reduction in the expressions of mitochondrial fission proteins DRP1, Nrf2, SIRT3, Caspase-3, Jun N-terminal Kinase (JNK)/P-JNK, NF-kappaB, Bcl2, and autophagic protein P62, as well as reduced ROS levels. Mdivi-1 had protective effects on the three common AKI cell models by potentially reducing mitochondrial fission in cells and inhibiting the production of ROS through the mediation of the NF- B/JNK/SIRT3 signaling pathway, thereby exerting protective effects. Key words AKI, Cisplatin, Gentamicin, Iohexol, Mdivi-1.
Keywords: Apoptosis; signální transdukce; Signal Transduction; reaktivní formy kyslíku; MAP Kinase Signaling System; lidé; MAP kinasový signální systém; sirtuin 3; Mitochondrial Dynamics; Acute Kidney Injury; apoptóza; Cell Line; mitochondriální dynamika; Humans; NF-kappa B; buněčné linie; akutní poškození ledvin; Reactive Oxygen Species; Sirtuin 3